2012
DOI: 10.9734/ajea/2012/1347
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Improved Sweet Potato (Ipomea batatas L.) Varieties in Makurdi, Southern Guinea Savanna of Nigeria

Abstract: Aim:To investigate the performance of some improved sweet potato varieties obtained from the National Root Crops Research Institute (NRCRI), Umudike, Nigeria, for root yield and other yield components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 4 publications
6
15
0
5
Order By: Relevance
“…Likewise the dry matter content of sweet potato roots was also negatively and highly significantly correlated (R = -0.65**) with number of branches per plant but positively and significantly correlated (R = 0.60 * ) with vine length. In agreement with the current result of our study, Egbe et al (2012) also found in their study, fresh weight was negatively and significantly associated (-0.66*) with number of branches per plant. Similarly a number of researches done by different researchers (Morita, 1969;Ravindran and Nambisa, 1987;Onwueme and Shinha, 1991), on different root and tuber crops found more vegetative growth including number of branches and leaves as well as vine length, as the expense of root and tuber initiation and development.…”
Section: Correlation Among Growth Parameters Of Ofsp Varietiessupporting
confidence: 93%
See 2 more Smart Citations
“…Likewise the dry matter content of sweet potato roots was also negatively and highly significantly correlated (R = -0.65**) with number of branches per plant but positively and significantly correlated (R = 0.60 * ) with vine length. In agreement with the current result of our study, Egbe et al (2012) also found in their study, fresh weight was negatively and significantly associated (-0.66*) with number of branches per plant. Similarly a number of researches done by different researchers (Morita, 1969;Ravindran and Nambisa, 1987;Onwueme and Shinha, 1991), on different root and tuber crops found more vegetative growth including number of branches and leaves as well as vine length, as the expense of root and tuber initiation and development.…”
Section: Correlation Among Growth Parameters Of Ofsp Varietiessupporting
confidence: 93%
“…The difference observed in number of branches per plant among the evaluated OFSP types is attributed to their genotypic difference. The current result is in conformity with the finding of Egbe et al (2012) who conclude that sweet potato variety, SPK004 gave significantly higher number (4.83) of branches per plant while sweet potato varieties, NASPOT 2 and NASPOT 4 gave the least number (3.83) of branches per plant. In line with the result of the current study, Mukhtar et al (2010) also stated that sweet potato variety, Dan Zaria produced significantly higher number of branches than variety Dan Bakalori and in similar study the highest number (13.67) of branch per plant was observed in variety CIP 441132 compared to the other varieties included in the study of Rahman et al (2013).…”
Section: Number Of Branches Per Plantsupporting
confidence: 93%
See 1 more Smart Citation
“…Berdasarkan beberapa penelitian pada ubijalar bobot per umbi, jumlah cabang, diameter umbi, dan panjang umbi berkorelasi positif dan nyata terhadap hasil umbi (Anshebo et al, 2004); bobot umbi per tanaman, indeks panen dan diameter umbi. berkorelasi positif dan nyata terhadap hasil umbi (Tsegaye et al, 2006); jumlah umbi berkorelasi positif dan nyata terhadap hasil umbi (Egbe et al 2012). Dalam penelitian ini, pendugaan keragaman genetik, heritabilitas dan sidik lintas antara berbagai karakter terhadap hasil digunakan untuk menentukan kriteria seleksi.…”
Section: Intisariunclassified
“…Hasil umbi memiliki korelasi positif dan nyata dengan bobot umbi per tanaman, indeks panen dan diameter umbi. (Tsegaye et al, 2006), dan jumlah umbi (Egbe et al 2012). Untuk mempelajari pengaruh langsung dan tidak langsung antara karakter agronomi dengan hasil umbi maka dilakukan analisis lintas (sidik lintas).…”
Section: Hasil Dan Pembahasanunclassified